ANALISIS SIKAP, KECEMASAN DAN HASIL BELAJAR MATEMATIKA SISWA - Ibrahim Ibrahim (Universitas Asahan, 2022)
Online learning carried out during this pandemic has a great opportunity to influence students' attitudes and anxiety in learning mathematics, which in turn affects mathematics learning outcomes. This study aims to: (1) determine the effect of attitudes on mathematics learning outcomes, (2) determine the effect of mathematics anxiety on mathematics learning outcomes, and (3) determine simultaneously the effect of attitudes and mathematics anxiety on mathematics learning. results. The research was conducted at SMPN 2 Ambal, Kebumen, Central Java, in the 2020/2021 school year, when learning from home was carried out due to the Covid-19 pandemic. The population of this study was all seventh-grade students of SMP Negeri 2 Ambal. Sampling used cluster random sampling so that a sample of 70 was obtained. The instruments used were mid-semester assessment tests, attitude scales, and math anxiety scales. This scale has been validated empirically. The F test and t-test were carried out by starting with the classical assumption test, namely normality, multicollinearity, and heteroscedasticity tests. This study concludes: (1) there is a positive effect of attitudes on mathematics learning outcomes, (2) there is a negative influence of mathematics anxiety on mathematics learning outcomes, and (3) there is a simultaneous influence of attitudes and mathematics anxiety on mathematics learning outcomes.